The impact of the application of polycentric knee modules on balance control and the level of mobility in trans-femoral amputation - Lončarić, Iva (Rehabilitacija (Ljubljana), 2016)
Introduction: The aim of prosthetics supply after trans-femoral amputation is restitution of body structure with the new biomechanical unit - a prosthesis constructed according to the needed level of stability and mobility. Technical performance of the modular solutions is in the focus of recent studies, but they lack information on the practical application and the impact of modular solutions on body functions. This paper reports on the influence of a polycentric knee module compared to the single-axis prosthetic knee on maintaining postural balance, mobility and independence in people with unilateral trans-femoral amputation. Methods: In the Department of Rehabilitation and Orthopaedics Aids of the University Hospital Centre Zagreb, an analysis of patients' functions data was carried out in order to determine changes in balance and mobility when using polycentric knee module as opposed to prosthetic supply with a single-axis knee module. The data were collected by assessing the patients at our Department before and during secondary prosthetic supply in the period from 2012 to 2015. Mobility and balance were tested with the Amputee Mobility Predictor (AMP) test with Medicare functional classification level, Berg's Balance Scale (BBS), Timed Up and Go (TUG) and 10-meter walk test. Results: A statistically significant difference was found regarding the TUG and 10-meter walk test between the patients with single axis knee compared to polycentric knee; the latter were faster on average. The average level of mobility according to AMP scoring was statistically significantly higher with the application of polycentric knee. Correspondingly, 10 of the 15 patients moved from lower to higher K-level according to Medicare functional classification level. The BBS results were also statistically significantly in favour of the polycentric knee module. Conclusion: Polycentric knee module for people with trans-femoral amputation allows better control of balance and speed as well as greater mobility in comparison with single-axis knee. For patients with trans-femoral amputation it thus provides a higher level of independence in activities of daily living.
Keywords: amputacija; Amputation; balance; body function; independence; lower limb amputation; Prostheses and Implants; prosthesis; proteza; ravnotežje; samostojnost; spodnji ud; telesne funkcije